Avaliação da toxicidade aguda e atividade antitumoral de lipossomas pH-sensíveis de longa circulação contendo cisplatina - Elaine Amaral Leite (2010)
Cancer is one of the main causes of mortality in the world, with chemotherapy being a valuable alternative for the disease treatment. Cisplatin (CDDP) is one of the most active cytotoxic agents and has been commonly used as first line chemotherapy against several tumors. However, the effectiveness of its clinical use is limited by severe side effects, mainly nephrotoxicity, and its tendency to provokechemoresistance. New nanostructured carriers, pH-sensitive and long-circulating liposomes containing CDDP were developed aiming to promove a more selective administration of CDDP to cancer cells that may contribute to a decrease in or elimination of toxicity and enhance its therapeutic efficacy. This work presents the pre-clinical evaluation of SpHL-CDDP focusing on acute toxicity after its administration by intravenous (IV) and intraperitoneal (IP) route in healtly Swiss miceand antitumoral efficacy after administration by IV route in Ehrlich solid tumorbearing Swiss mice. For acute toxicity study, animals received different doses of free CDDP or SpHL-CDDP and the parameters evaluated included: body weight variation, LD50 and maximum tolerated dose (MTD) determination, hematological and biochemical analysis as well as histopathological evaluation of kidneys, liver, spleen and bone marrow. The results showed a greater loss of body weight in micetreated with free CDDP than those treated with SpHL-CDDP, after administration by IP and IV route. The LD50 and MTD were significantly increased in male and female mice after SpHL-CDDP treatment compared with free CDDP treatment, in both routes investigated. Hematological parameters alterations were observed afteradministration of low doses of free CDDP (5 and 10 mg/kg) by IP route, while by IV route these alterations only occurred after the administration of high doses (20 mg/kg). These findings associated to the morphological alterations confirmed the mielossupressor effect of CDDP treatment. On the other hand, SpHL-CDDP treatment provoked no modification over hematological parameters indicating the absence of myelotoxicity. As regards nephrotoxicity, free CDDP treatment caused significant alterations in the blood urea, creatinine levels and urea/creatinine index of male and female mice. In addition, the microscopic examination of kidneys revelead a severe toxic tubular necrosis. In contrast, slight alterations of biochemistry parameters and absence of histopathological modifications were observed in mice 29 treated with SpHL-CDDP. No morphological alteration of liver and spleen was observed after both treatments by two routes used. Concerning antitumoral activity,Ehrlich solid tumor-bearing Swiss mice received three doses of SpHL-CDDP (16 mg/kg) or free CDDP (8 mg/kg) by IV route and the tumor volume was evaluated along time as well as the histomorphological characterization of tumor was performed. The treatment with SpHL-CDDP inhibited significantly the growth of tumor volume in comparison with free CDDP. No difference in the histomorphometrical features has been detected. Therefore, SpHL-CDDP treatment showed to be less toxic than free CDDP treatment allowing to increase the administered dose, and consequently, to achieve a greater pharmacological effect than that observed after free CDDP treatment. These results demonstrated that SpHL-CDDP is a promising candidate for chemotherapy of tumors which are sensitive to CDDP treatment. Key-words: cisplatin, pH-sensitive and long-circulating liposomes, acute toxicity, antitumoral efficacy